2019
DOI: 10.18196/pt.2019.097.82-92
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Dried Cocoa Beans (Theobroma cacao L.) Color Using Response Surface Methodology

Abstract: The research aimed to study the effects of storage time of cacao fruit before fermentation, aeration rate and temperature of fermenter during fermentation on the color value of dry cocoa beans, including the value of L *, a *, b *, chroma, hue, and RGB, and their relationship using response surface methodology.. The results showed that storage time of cacao fruits before fermentation, aeration rate and temperature of the fermenter had an influence on the color values of L *, a *, b *, chroma, hue, and RGB of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
0
6
0
1
Order By: Relevance
“…Żyżelewicz et al (2014) reported that the cocoa beans of Forastero cultivar from Togo showed the following chromatic values (L* = 34.69; a* = 5.52; b* = 2.68). According toHartuti et al, (2019) the chromatic parameters of fermented dried cocoa beans at different temperatures and times showed the following values(L* = 31.64-48.56; a* = 11.06-20.54; b* = 8.65-18.76; C*ab = 16.50 -27.64; hab = 30.01°-51.73°).…”
mentioning
confidence: 99%
“…Żyżelewicz et al (2014) reported that the cocoa beans of Forastero cultivar from Togo showed the following chromatic values (L* = 34.69; a* = 5.52; b* = 2.68). According toHartuti et al, (2019) the chromatic parameters of fermented dried cocoa beans at different temperatures and times showed the following values(L* = 31.64-48.56; a* = 11.06-20.54; b* = 8.65-18.76; C*ab = 16.50 -27.64; hab = 30.01°-51.73°).…”
mentioning
confidence: 99%
“…This study consisted of 2 treatment factors/variables, then the F value was equal to 2² = 4, so that according to Equation 1, it was obtained α = (4) 1/4 = 1.414 and the value of ± 1.414 including the value used for coding. At this stage a mathematical equation will be formed with a second-order polynomial model whose functions are quadratic [5], [6]as follows (equation 2). Where, Y is the value of the treatment response (colour, aroma, flavour, and after taste), βo is the intercept/constant, β1,and β2,are linear coefficients, β11andβ22are quadratic coefficients, andβ12, is the treatment interaction coefficient, namely the amount of water (X1) and the amount of tea (X2).The calculation of the value of ± α for the variables X1 and X2 in the research was obtained based on the calculation of the difference in the value of level (+1) or level (-1) against level (0) and multiplied by 1.414 (α) plus the level value (0) as follows:…”
Section: Experimental Design and Analysismentioning
confidence: 99%
“…Color is one of the visual parameters that can provide information about the product (Hartuti et al, 2019). In addition, a product's color is correlated with product profile attributes such as sensory and nutritional content (Pathare et al, 2012).…”
Section: Colormentioning
confidence: 99%